Comparative Study of Students' Conceptual Understanding in Two Different Curricula on the Light and Electromagnetic Waves Materials - Melati, Bunga Chinta; Permana Suwarna, Iwan; Hertanti, Erina (Jurnal Pendidikan Matematika dan Sains, 2025)
Conceptual understanding involves a deep comprehension of a concept, including the ability to explain, illustrate, and apply it in various contexts. This study aims to compare students’ levels of conceptual understanding under the Kurikulum Merdeka and the Cambridge Curriculum. A comparative descriptive method with a mixed-methods approach was used, employing a six-tier diagnostic test, interviews, and classroom observations. The sample consisted of 60 students selected through purposive sampling. The results showed that students following the Kurikulum Merdeka had a higher percentage of scientific understanding (43.4%) compared to those in the Cambridge Curriculum (20.3%). These findings indicate that the effectiveness of instruction is influenced not only by the curriculum strategy but also by factors such as the timing between instruction and assessment, students’ confidence in their responses, and language barriers. Therefore, instructional approaches should be aligned with students’ cognitive readiness and contextual conditions to optimize conceptual understanding.